3D polymer objects with electronic components interconnected via conformally printed electrodes. Issue 39 (28th September 2017) - Jo, Yejin; Kim, Ju Young; Jung, Sungmook; Ahn, Bok Yeop; Lewis, Jennifer A.; Choi, Youngmin; Jeong, Sunho
Abstract : We report the fabrication of 3D polymer objects that contain electrical components interconnected by conductive silver/carbon nanotube inks printed conformally onto their surfaces and through vertical vias. Abstract : We report the fabrication of 3D polymer objects that contain electrical components interconnected by conductive silver/carbon nanotube inks printed conformally onto their surfaces and through vertical vias. Electrical components are placed within internal cavities and recessed surfaces of polymer objects produced by stereolithography. Conformally printed electrodes that interconnect each electrical component exhibit a conductivity of ∼2 × 10 4 S cm −1 upon annealing at temperatures below 100 °C. Multiple 3D objects were created to demonstrate this hybrid additive manufacturing approach, including those with an embedded circuit operated by an air-suspended switch and a 3D circuit board composed of microcontroller unit, resistor, battery, light-emitting diode and sensor.